Anything but okay - Littman, Sarah (Scholastic Press, 2018)
Life has suddenly turned chaotic for high school student Stella since her brother, Rob, got home from his second tour of duty in Afghanistan: her school is on edge with ethnic tensions and her brother seems to be suffering from post-traumatic stress but will not talk about it. But when Rob's anger finally spirals out of control, Stella realizes she has to find the courage to take a stand against the forces of hate in her hometown.